X3 synthon geometries in two-dimensional halogen-bonded 1, 3, 5-tris(3, 5-dibromophenyl)benzene self-assembled nanoarchitectures on Au(111)-(). Issue 6 (10th January 2018) - Peyrot, David; Silly, Mathieu G.; Silly, Fabien
Abstract : Star-shaped 1, 3, 5-tris(3, 5-dibromophenyl)benzene molecules self-assemble into 2D nanoarchitectures stabilized by two types of halogen interactions on Au(111)-( ). Abstract : The self-assembly of star-shaped 1, 3, 5-tris(3, 5-dibromophenyl)benzene molecules on Au(111)-( ) in a vacuum is investigated using scanning tunneling microscopy and core-level spectroscopy. Scanning tunneling microscopy shows that the molecules self-assemble into a hexagonal porous halogen-bonded nanoarchitecture. This structure is stabilized by X3-A synthons composed of three type-II halogen-interactions (halogen-bonds). The molecules are oriented along the same direction in this arrangement. Domain boundaries are observed in the hcp region of the herringbone gold surface reconstruction. Molecules of the neighboring domains are rotated by 180°. The domain boundaries are stabilized by the formation of X3-B synthons composed of two type-II and one type-I halogen-interactions between molecules of the neighboring domains. Core-level spectroscopy confirms the existence of two types of halogen-interactions in the organic layer. These observations show that the gold surface reconstructions can be exploited to modify the long-range supramolecular halogen-bonded self-assemblies.